ANALISIS KETERKAITAN NARCISSISM TERHADAP TAX EVASION DENGAN MORAL DISENGAGEMENT SEBAGAI VARIABEL INTERVENING - Sekar Lintang Timur; Nur Cahyonowati (Diponegoro Journal of Accounting, 2025)
Personality is an inherent trait in every individual. In addition to personalities that are considered positive, there are also negative ones known as the dark triad, one of which is narcissism that is often associated with immoral behavior. This study aims to examine the effect of narcissistic personality on tax evasion through moral disengagement as a mediating factor. This research uses a quantitative approach and survey questionnaire method through Google Form to individual taxpayers registered at the tax office in Central Java Province. The number of samples used was 384 respondents and the data were analyzed using Structural Equation Modeling (SEM) with WarpPLS 8.0 software. The results of the study show that narcissism does not have a positive effect on tax evasion. In contrast, narcissism has a positive effect on moral disengagement. Furthermore, moral disengagement has a positive impact on tax evasion. Lastly, narcissism has a positive effect on tax evasion through moral disengagement as a fully mediating factor.